Comparison of the effects of antiarrhythmic drugs flecainide and verapamil on fKv1.4△N channel currents in Xenopus oocytes - Chen, Hui; Zhang, Dong; Chao, Sheng-ping; Ren, Jiang-hua; Xu, Lin; Jiang, Xue-jun; Wang, Shi-min (Acta pharmacologica Sinica, 2013)
Aim： To study the effects of Na＋ channel blocker flecainide and L-type Ca^2＋ channel antagonist verapamil on the voltage-gated fKvl.4AN channel, an N-terminal-deleted mutant of the ferret Kvl.4 K＋ channel. Methods： fKvl.4hN channels were stably expressed in Xenopus oocytes. The K^＋ currents were recorded using a two-electrode voltage-clamp technique. The drugs were administered through superfusion. Results： fKvl.4AN currents displayed slow inactivation, with a half-inactivation potential of -41.74 mV and a slow recovery from inactivation （T=1.90 S at -90 mV）. Flecainide and verapamil blocked the currents with ICso values of 512.29＋56.92 and 260.71＋18.50 pmol/L, respectively. The blocking action of the drugs showed opposite voltage-dependence： it was enhanced with depolarization for flecainide, and was attenuated with depolarization for verapamil. Both the drugs exerted state-dependent blockade on fKvl.4AN currents, but verapamil showed a stronger use-dependent blockage compared with flecainide. Flecainide accelerated the C-type inactivation rate without affecting the recovery kinetics and the steady-state activation. Verapamil also accelerated the inactivation kinetics of the currents, but unlike flecainide, it affected both the recovery and the steady-state activation, causing slower recovery of fKvl.4AN channel and a depolarizing shift of the steady-state activation curve. Conclusion： The results demonstrate that widely used antiarrhythmic drugs flecainide and verapamil substantially inhibit fKvl.4hN channels expressed in Xenopus oocytes by binding to the open state of the channels. Therefore, caution should be taken when these drugs are administered in combination with K^＋ channel blockers to treat arrhythmia.